Influence of Sintering Temperatures on Structure and Electrical Conductivity of TiO2 Cathode - Li, Zequan; Zhang, Na; Bai, Chenguang; Jian, Dongmei; Ru, Liyue; Wang, Haihua (Asian Journal of Chemistry, 2011)
The influence of sintering temperatures on the structure and electrical property of TiO2 cathode was investigated with regards to the crystal structure and composition, microstructure, oxygen vacancies, surface properties and electrical conductivity. The as-products were characterized by powder X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), digital four-point probe conductivity instrument (DFFPCI) and accelerated surface area and porosimetry system (ASAP). XRD analysis confirms that anatase phase TiO2 at 700 ºC transformed to rutile phase TiO2 and TiO1.95 with the increase of sintering temperatures to 850 ºC and 950 ºC. The Ti°Cp binding energy of TiO2, as studied by XPS, is discussed in terms of the valence state of the titanium ions. Digital four-point probe conductivity instrument analysis indicate that the electrical conductivity increase with the rise of temperature. Scanning electron microscopy and accelerated surface area and porosimetry system analysis indicate that the grain of the obtained TiO2 increase but nitrogen storage properties decrease with the increase of sintering temperatures. Moreover, the experimental results show that the electrical conductivity of TiO2 increases with the rise of the temperature.